Endoscopic Distal Tibiofibular Syndesmosis Arthrodesis - Lui, Tun Hing (Arthrosc Tech, 2016)
Chronic distal tibiofibular syndesmosis disruption can be managed by endoscopic arthrodesis of the syndesmosis. This is performed through the proximal anterolateral and posterolateral portals. The scar tissue and bone block are resected to facilitate the subsequent reduction of the syndesmosis. The reduction of the syndesmosis can be guided either arthroscopically or endoscopically. The tibial and fibular surfaces of the tibiofibular overlap can be microfractured to facilitate subsequent fusion.